First measurement of D*+ vector meson spin alignment in Pb-Pb collisions at TeV - Acharya, S.; Agarwal, A.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; Akishina, V.; et al. (SPRINGER, 2025)
The first measurement of prompt D*+-meson spin alignment in ultrarelativistic heavy-ion collisions with respect to the direction orthogonal to the reaction plane is presented. The spin alignment is quantified by measuring the element rho(00) of the diagonal spin-density matrix for prompt D*+ mesons with 4 1/3 has been found for p(T)> 15 GeV/c and 0.3 < |y| < 0.8 with a significance of 3.1 sigma. The measured spin alignment of prompt D*+ mesons is compared with the one of inclusive J/psi mesons measured at forward rapidity (2.5 < y < 4).
Keywords: Heavy Ion Experiments; Particle Correlations and Fluctuations; QCD; Quark Gluon Plasma; MAGNETIC-FIELD; Physics